2009
DOI: 10.1101/gad.1864609
|View full text |Cite
|
Sign up to set email alerts
|

Subtraction by addition: domesticated transposases in programmed DNA elimination: Figure 1.

Abstract: The ciliate Paramecium tetraurelia must eliminate ∼60,000 short sequences from its genome to generate uninterrupted coding sequences in its somatic macronucleus. In this issue of Genes & Development, Baudry and colleagues (pp. 2478–2483) identify the protein that excises these noncoding sequences: a domesticated piggyBac transposase that has been adapted to remove what are likely the remnants of transposon insertions. This new study reveals how addition of a transposase to small RNA-directed silencing mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The strain might be a highly proliferative variant, with distinct cell cycle control or which undergoes macronuclear differentiation involving heightened gene amplification, above that found in other variants. Although recent studies have shed light on the mechanisms of macronuclear development in ciliate species (Nowacki et al 2008, Motl & Chalker 2009, there are currently no reported studies of the mechanisms that operate during macronucleus formation in M. rubra. Exploration of the nuclear dualism of M. rubra might provide clues to the highly proliferative nature of the bloom-forming variants of M. rubra.…”
Section: Discussionmentioning
confidence: 99%
“…The strain might be a highly proliferative variant, with distinct cell cycle control or which undergoes macronuclear differentiation involving heightened gene amplification, above that found in other variants. Although recent studies have shed light on the mechanisms of macronuclear development in ciliate species (Nowacki et al 2008, Motl & Chalker 2009, there are currently no reported studies of the mechanisms that operate during macronucleus formation in M. rubra. Exploration of the nuclear dualism of M. rubra might provide clues to the highly proliferative nature of the bloom-forming variants of M. rubra.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature differentiating HO from true homing endonucleases is that it does not propagate its own DNA sequence – in other words, it does not home. HO has become a normal cellular gene, and is one of the many known examples of a mobile genetic element that has been domesticated to take on a new role (Volff, 2006; Kaiser et al, 2009; Motl and Chalker, 2009; McDowell and Meyers, 2013; Chiruvella et al, 2016; Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable prediction as to which sequences may be more amenable to SGV could first consider (retro)transposons, then elements such as LINEs and SINEs, especially those sequences known or suspected to assume anomalous non-B conformations [ 44 , 48 ]. It has been reported that, in the spectrum of the events responsible for human genome variations, deletions are more frequent than insertions or other rearrangements [ 49 ]: this is reasonable and may reflect a compensatory removal of sequences following synthetic (retro)transpositions otherwise responsible of an unbearable overgrowth of the genome size [ 50 ]. Relevant to this is the observation that during development: “The set of genes deleted is not random in the (human) genome; there is a clear association with segmental duplications among larger deletion events.…”
Section: State Of the Artmentioning
confidence: 99%